Genetics of iron regulation and the possible role of iron in Parkinson's disease - Shannon L. Rhodes; Beate Ritz (Neurobiology of Disease, 2008)
Parkinson's disease (PD) is acknowledged as the second most common neurodegenerative disorder after Alzheimer's Disease. Older age may be the only unequivocal risk factor for PD although the male to female ratio is consistently greater than 1 in populations of European ancestry. Characteristic features of PD include dopaminergic neuron death in the substantia nigra (SN) pars compacta, accumulation of α-synuclein inclusions known as Lewy bodies in the SN, and brain iron accumulation beyond that observed in non-PD brains of a similar age. In this review article, we will provide an overview of human and animal studies investigating the contributions of iron in PD, a summary of human studies of iron-related genes in PD, a review of the literature on the genetics of iron metabolism, and some hypotheses on possible roles for iron in the pathogenic processes of PD including potential interactions between iron and other factors associated with Parkinson's disease.